Computational Model Applied to the Behavior of Financial Agents Using Cellular Automata (Cell-DEVS) - Barrantes Limahuaya, Jesús (2018)
In the present paper, the effect of interdependence and contagion will be performed in the purchase and sale decisions of investors in a Black-Schole financial market, where there are two financial assets: stocks (risky assets) and bonds (risk-free asset); and two investor states: lover and risk aversion; under different probabilities of contagion. This economic-financial phenomenon could be modeled by a system of stochastic equations; however, not all stochastic equations have a closed solution, so it is decided to perform computational simulations to analyze their numerical behavior. In this sense, a computational simulation will be performed using cellular automata.